MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH MELALUI METODE VAKT DENGAN MEDIA PLASTISIN BAGI ANAK TUNAGRAHITA RINGAN - Dian Siswanti (Jurnal Penelitian Pendidikan Khusus, 2012)
This approach uses experimental approaches in the form of Single Subject Research (SSR) with the design of A - B subjects were mild Tunagrahita child DIV class R / C. Research in this study are consistent and measured the number of correct answers in reading letters hijaiyah child who is in the letter presented in the form hijaiyah namber. The results of this study indicate that children's ability in reading the letter R Tunagrahita hijaiyah increased initially performed at baseline conditions in the seven-time observations. Children who can answer the four letters that researchers give to the four letters are the letters alif (1), ba (ب), ta (ت), Tsa (ث). So in the baseline condition of the child can only read the letters hijaiyah until Tsa (ث). For the intervention condition literacy rate of change is increasing hijaiyah letter, which the child can answer all the questions that researchers are given, meaning that children can read the letter that investigators hijaiyah limit to syin (ش). correctly. Thus proved that the method VAKT with Platicin media effectively to improve literacy skills in children Tunagrahita hijaiyah lightweight class D R / V / C in PLB Limas Padang. In connection with this research. So the researchers suggest to the teacher to use the media Platicin VAKT method for further learning.